Literature Review: Faktor Risiko Hipertensi di Indonesia - Dewati, Carissa Auliya; Natavany, Azarine Raissa; Putri, Zhafira Marifta; Nurfaizi, Almas; Rumbrawer, Sila Olivia; Sri Rejeki, Dwi Sarwani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Currently, hypertension is still a concern for all people both living in rural and urban areas. Hypertension is a state of increased systolic blood pressure >140 mmHg and systolic blood pressure >90 mmHg on two measurements in a relaxed state with an interval of five minutes. Thir research was conducted with the aim of studying scientific articles related to hypertension risk factors in Indonesia. The research design used is literature review with article inclusion criteria containing risk factors of hypertension incidence in Indonesia from 2018-2022, while the exclusion criteria used is not related to the topic of hypertension risk factors in Indonesia. The data and information are obtained through the Google Scholar and PubMed databases with the keywords hypertension, risk factors, age, gender, lifestyle, physical activity, diet, and Indonesia. Based on the results of this study, the dominant risk factors of hypertension in Indonesia are physical activity, excess intake of sugar, salt, and fat.